2013
DOI: 10.1111/jcpe.12070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immediate loading on early bone healing at two‐piece implants placed in fresh extraction sockets: an experimental study in the beagle dog

Abstract: Immediate loading did not impair early stages of bone healing and crestal bone modelling at two-piece implants in fresh extraction sockets in the beagle dog; however, bone resorption occurred in all specimens in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
(78 reference statements)
7
18
0
Order By: Relevance
“…Several preclinical studies assessing the impact of loading on the implants' osseointegration showed that the replacement of the old bone occurred more rapidly and with greater bone-implant contact (Vandamme et al, 2007;Esaki et al, 2012;Blanco et al, 2013;Yamamoto et al, 2013). These conclusions could be associated with the altered release of bone markers in IM implants, which are seen in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Several preclinical studies assessing the impact of loading on the implants' osseointegration showed that the replacement of the old bone occurred more rapidly and with greater bone-implant contact (Vandamme et al, 2007;Esaki et al, 2012;Blanco et al, 2013;Yamamoto et al, 2013). These conclusions could be associated with the altered release of bone markers in IM implants, which are seen in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Several experiments evaluating the effect of loading on osseointegration also have been performed in various animal models, such as monkeys, dogs, pigs and rabbits . Some experiments evaluated osseointegration when a physiologic load was applied .…”
Section: Discussionmentioning
confidence: 99%
“…Also, various animal experiments have attempted to analyse the effect of immediately or delayed loading on osseointegration …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the immediate loading protocol applied in Type I (immediate) implant installation (Blanco et al. , ) has shown similar results in buccal bony crest height and osseointegration in loaded and unloaded sites.…”
mentioning
confidence: 90%